Experimental and numerical investigation of heat transport and hydrodynamic properties of 3D-structured catalytic supports. (5th November 2017) - Danaci, Simge; Protasova, Lidia; Try, Rasmey; Bengaouer, Alain; Marty, Philippe
Graphical abstract: Highlights: The higher heat transport and lower pressure drop can be obtained with 3D-structured supports. The main parameter influencing the effective thermal conductivity was found to be the macroporosity. The stacking affects the effective thermal conductivity due to the difference in the connection between the fibres. The zig-zag fibre stacking have higher pressure drop values than the samples with parallel fibre stacking at the same macroporosity. Abstract: In this work, heat transport and pressure drop properties of 3D-manufactured stainless steel structured catalytic supports are described based on experimental data and modelling. The effective thermal conductivity was determined at temperatures between 50 and 500 °C by diffusivity measurements. For the samples with 74% macroporosity, at temperatures from 50 to 500 °C, axial and radial effective thermal conductivities range between 1.78–2.5 and 1.83–2.87 W⋅m −1 ⋅K −1, respectively. The effect of geometry (fibre stacking, fibre diameter and macro-porosity) on the effective thermal conductivity was experimentally determined and compared to the modelling results. The main parameter influencing the effective thermal conductivity was found to be the macroporosity. The effect of the geometry (fibre stacking) and the coating thickness on the pressure drop were studied experimentally. The pressure drop was measured by a manometer with air as a fluid gas. Pressure drop measurements showed that the samples with zig-zag fibre stacking (1-3 stacking) have higher pressure drop values than the samples with straight fibre stacking (1-1 stacking) at the same macroporosity due to their lower open frontal area.